Metabolic recovery in professional road cyclists: A 31P-MRS study - Hug, F.; Bendahan, D.; Le Fur, Y.; Cozzone, P. J.; Grelot, L. (Medicine & Science in Sports & Exercise, 2005)
Purpose: Aerobic training of professional road cyclists is linked to tremendous aerobic capacities that have never been clearly related to what occur in skeletal muscles submitted to a specific exercise. The aim of the present study was to examine specifically metabolic recovery after an incremental cycling exercise performed until exhaustion in professional road cyclists as compared with moderately trained subjects and so using 31P- MRS.